2012
DOI: 10.1890/es12-00054.1
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of pollen clump release and breakup in the vicinity of ragweed (A. confertiflora) staminate flowers

Abstract: Pollen dispersal is fundamental in a plant's reproductive ecology and as a result of fragmentation of the landscape, questions have been raised on how isolated plant populations can still exchange genetic information. A common mechanism for gene exchange is wind pollination (anemophily). A successful anemophilous species native to North America is ragweed (Ambrosia), a weed that is hard to eradicate after it takes root on crop fields and its pollen causes very strong allergenic effects (hay fever). Despite the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 69 publications
0
8
0
1
Order By: Relevance
“…Other functions for mucilage are plausible and can even co‐occur, such as (1) to prevent the tissue rupture in the organs that move very quickly in this complex mechanism of explosive release of the pollen; (2) to prevent the rapid desiccation of the released pollen (see Fahn and Cuttler, ) and, consequently, the loss of pollen longevity since in some species of Urticaceae the pollen grain is considered partially hydrated (Franchi et al., ), and (3) to agglutinate the released pollen, guaranteeing that large amounts of pollen are deposited on the stigma of a pistillate flower (Sabban et al., ; Timerman et al., ), thus improving pollen competition. The last two propositions are supported by the fact that the process of anther dehiscence begins before filament distension, which would allow the contact of the pollen grains with the various floral organs that produce mucilage.…”
Section: Discussionmentioning
confidence: 99%
“…Other functions for mucilage are plausible and can even co‐occur, such as (1) to prevent the tissue rupture in the organs that move very quickly in this complex mechanism of explosive release of the pollen; (2) to prevent the rapid desiccation of the released pollen (see Fahn and Cuttler, ) and, consequently, the loss of pollen longevity since in some species of Urticaceae the pollen grain is considered partially hydrated (Franchi et al., ), and (3) to agglutinate the released pollen, guaranteeing that large amounts of pollen are deposited on the stigma of a pistillate flower (Sabban et al., ; Timerman et al., ), thus improving pollen competition. The last two propositions are supported by the fact that the process of anther dehiscence begins before filament distension, which would allow the contact of the pollen grains with the various floral organs that produce mucilage.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, pollen may be removed passively from the anther by aerodynamic forces (e.g. lift and drag) acting directly on pollen grains within a dehisced anther [9,13,14]. A third possibility, to be explored here, is that agitation of stamens or their supporting scapes or catkins by turbulent winds leads to accelerations sufficient to expel grains into the air column [7,9,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a larger clump would be more susceptible to the force of drag (proportional to frontal area), would project farther into the boundary layer, and thus would be more likely to abscise. Interestingly, only two empirical studies of release in relation to PDU size have been undertaken, and both found that pollen release was enhanced by aggregation in the anemophilous Ambrosia (Martin et al 2009;Sabban et al 2012). In contrast to anemophily, pollen aggregation is advantageous in biotic pollination (Pacini 2000;Harder and Johnson 2008), as it can, for example, improve siring success by increasing the adhesion of pollen to floral visitors (via adhesive substances), reducing pollen loss during grooming (via threaded pollen or pollinia), and delivering multiple pollen grains to stigmas (e.g., zoophilous ovaries are often multiovulate, whereas anemophilous ovaries are invariably uniovular).…”
Section: International Journal Of Plant Sciencesmentioning
confidence: 99%